PENERAPAN STRATEGI PEMBELAJARAN SCAFFOLDING UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK PADA MATERI MOMENTUM, IMPULS DAN TUMBUKAN KELAS X SMA N 12 PEKANBARU - Norma Sari; Mitri Irianti; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was aimed to determine the improvement of students' concept understanding by the application of scaffolding learning strategy. The type of this study was quasy experiment with intact group comparison design. The population in this study were the X grade students of SMA Negeri 12 Pekanbaru which consisted of 4 classes. 2 classes were chosen as the sample of study as experiment and control class based on normality and homogenity tests. The data was collected by giving the test of concept understanding which were consisted of 7 questions based on the indicators of concept understanding. The data was analized by descriptive and inferential analysis. The result of this study showed that there was a significant difference toward the ability of concept understanding between control class which was applied scaffolding learning strategy and control class which was taugh by conventional learning. The concept understanding of experiment class' students were higher than control class. It can be concluded that the scaffolding learning strategy could improve the students' concept understanding.Keywords: Scaffolding learning stategy, concept understanding, momentum, impulse and collision.